2022
DOI: 10.3389/fmars.2022.879953
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Automatic Water Autosampler Operated From UAVs for Determining Dissolved Trace Elements

Abstract: Monitoring water systems under extreme conditions or in remote areas poses a risk to scientists and staff involved, and can also result in disturbances to the local flora and fauna. In order to overcome these limitations, new techniques are being developed with the aim to gain more insight into how geochemical pathways of trace elements regulate the functioning of the ocean. Here, we present the first trace metals and inorganic nutrients concentrations measured in dissolved (<0.22 µm) surface water samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…We found that according to the 16,725 ± 907 penguins censed by the model, a total of 169.4 t of dry weight guano can be expected in the breeding site considering 120 days as the breeding season duration, containing up to 512 ± 246 kg Fe (see Methods). Subsequently, considering the Fe concentration (0.324 mg L −1 ) 38 in the coastal water at the specific time of study, we obtained an approximate Fe content of 26 kg in 8 × 10 4 m 3 of water under the influence of the Chinstrap penguin turbidity plume (Fig. 2a, b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that according to the 16,725 ± 907 penguins censed by the model, a total of 169.4 t of dry weight guano can be expected in the breeding site considering 120 days as the breeding season duration, containing up to 512 ± 246 kg Fe (see Methods). Subsequently, considering the Fe concentration (0.324 mg L −1 ) 38 in the coastal water at the specific time of study, we obtained an approximate Fe content of 26 kg in 8 × 10 4 m 3 of water under the influence of the Chinstrap penguin turbidity plume (Fig. 2a, b ).…”
Section: Resultsmentioning
confidence: 99%
“…During the campaign, one sampling was performed in the VC colony 38 , in a shore area in the vicinity of various depressions between hills which act like “funnels”, both for penguins to go to/from the nests, and for guano runoff to the ocean. The sampling location was used as a starting point from which the volume of water influenced by the guano release was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal camera captures non-contact temperature measurements with calibrated temperature data embedded in every pixel, its spectral band is 7.5-13.5 μm and it has a sensor resolution of 336 × 256. In addition, this UAV was equipped with a water sampling device (Sparaventi et al, 2022) with an acid cleaned plastic weighted container (2 L) and a castable instrument hanging from the UAV with a 5-meter rope providing instantaneous profiles of temperature and salinity (CastAway R -CTD) and collected surface water.…”
Section: Uav Platforms and Sensorsmentioning
confidence: 99%
“…The survey (February 8, 2021) coincided with the end of the breeding season, when penguins tend to leave the colony and therefore the deep learning census corresponded to the lower limit of the whole nesting period. Subsequently, considering the Fe concentration (0.324 mg L -1 (31) ) in the coastal water at the specific time of study, we obtained an approximate Fe content of 26 kg in 8×10 4 m 3 of water under the influence of the Cp plume (Fig. 2a, b).…”
Section: Water Iron Enrichment Through Penguin Guanomentioning
confidence: 99%